(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1995)
Twenty-seven Tertiary species belonging to the cosmopolitan reef-building scleractinian genus Actinacis, have been described in the literature. A detailed systematic revision has been carried out for Italian and European species by thin section measurements of material mostly sampled from several Italian localities by observation of some holotypes and topotypes and accurare examination of the available literature. A combination of several measured corallite morphologic characters and diagnostic features is proposed as a reliable tool for species recognition. Results indicate that only three species, of the twelve described for the Italian Tertiary sites, actually belong to the genus Actinacis. Moreover, a list of synonyms and a stratigraphic range chart of the established species are proposed. An approximate taxonomic identification and stratigraphic distribution are given for those species not included in the systematic revision. Preliminary examination of the stratigraphic and geographic distribution of Actinacis species suggests that:1) the Tertiary distribution of the genus ranges from the Late Paleocene to the Late Oligocene (from Late Cuisian to Middle Chattian as concerns ltaly); 2)the highest species diversity occurred during the Middle Eocene, when the genus consisted of a relatively large number of geographically restricted species; 3) only two widespread species survived the Eocene/Oligocene turnover and reached the Late Oligocene, when the genus became globally extinct.